Breeding population of the Rook "Corvus frugilegus" in the Mazovian Lowland: current status and changes - Chmielewski, Sławomir; Dombrowski, Andrzej; Jabłoński, Piotr; Łukaszewicz, Marcin; Nicewicz, Łukasz; Trębicki, Łukasz; Pagórski, Piotr; Tabor, Jacek (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
In 2012-2015 nests of the Rook "Corvus frugilegus" were counted in the Mazovian Lowland area (42,379 km2). A total of 69,442 nests on 693 sites were found. The overall population was estimated at 72,125-76,488 nests. The average rookery size reached 100.2 nests (SD = 192.4). There were five colonies (0.7%) with at least 1,000 nests, 368 (52.4%) small colonies with up to 25 nests, 32 (4.6%) sites with single nests and 103 (14.9%) with up to 3 nests. 83% of all nests were located in rookeries with more than 100 nests (26% of all colonies).
Keywords: Rook; Corvus frugilegus; Mazovian Lowland; population size; population density; habitat preferences